(3YeGO GdQVG HHjGf BOGH GdbVGs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s; (3TQa GdOjf YjSi Hf YKeGf GdZRjs ((3TjN Hf Ydi Hf eMeO MaQi s)
(3ChdgG (B:s
(3hHYO adeG cGf ai COH GdbVG ddYdGeI TQa GdOjf YjSi GdZRi eG Zfg ZfG eY GMJjGLg Edi JMQjQ GNJUQJg eMQQkG eY RjGOGJ MSfg hSeJjg YeGO GdQVG HHjGf COH GdbVG s
(3BNQgG (B:s
(3hEf cGf dh UQM Hg de jbHd ai HGH GdTgGOGJ s
(3GdfSNI HgG MhGTs
(3fSNI QGHYIs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B53s
Keywords: (3GdQjGVjGJs